2011
DOI: 10.1245/s10434-011-2020-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Postoperative Serum CA 19-9 Levels in Patients with Resectable Pancreatic Cancer

Abstract: Postoperative CA 19-9 level was associated with positive surgical margin and hepatic or peritoneal recurrence and may be a useful predictor for survival in patients with pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 18 publications
6
56
1
Order By: Relevance
“…The results of our study also showed that there were greater significant differences in MTV and TLG than in SUVmax between patients with and without recurrence and that only MTV and TLG were independent prognostic factors for both RFS and OS among the 18 F-FDG PET/CT parameters analyzed. Several prognostic factors for predicting recurrence of pancreatic cancer have been suggested, and tumor size, pT stage, lymph node metastasis, tumor differentiation, lymphovascular invasion, and serum CA19-9 level have been shown to be significant predictors (1,(7)(8)(9). Because exact tumor size, pT stage, presence of lymph node metastasis, tumor differentiation, and lymphovascular invasion of the tumor can be assessed only by examining the surgical specimen, they cannot be used to predict clinical outcomes before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study also showed that there were greater significant differences in MTV and TLG than in SUVmax between patients with and without recurrence and that only MTV and TLG were independent prognostic factors for both RFS and OS among the 18 F-FDG PET/CT parameters analyzed. Several prognostic factors for predicting recurrence of pancreatic cancer have been suggested, and tumor size, pT stage, lymph node metastasis, tumor differentiation, lymphovascular invasion, and serum CA19-9 level have been shown to be significant predictors (1,(7)(8)(9). Because exact tumor size, pT stage, presence of lymph node metastasis, tumor differentiation, and lymphovascular invasion of the tumor can be assessed only by examining the surgical specimen, they cannot be used to predict clinical outcomes before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most patients who undergo resection with curative intent develop recurrence usually in the first 6-12 mo of the surgery (4)(5)(6). Several prognostic factors for pancreatic cancer recurrence have previously been reported including tumor size, T stage, lymph node metastasis, tumor differentiation, lymphovascular invasion, involvement of the surgical margin, and serum carbohydrate antigen 19-9 (CA19-9) level (1,(7)(8)(9).…”
mentioning
confidence: 99%
“…5 Our data from seven high-volume surgical institutions in Japan during a 22 demonstrated that the presence of perineural invasion was the single independent variable significantly associated with an increased risk of peritoneal recurrence. Hata et al 23 showed that the postoperative CA19-9 level was associated with positive surgical margins and hepatic or peritoneal recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is often discordance between histological characteristics, tumour stage and survival [4,5]. Serum carbohydrate antigen remains the only biomarker used in clinical practice to monitor disease progression during PDAC treatment [2], with elevated levels post-operatively correlated with resection margin positivity (R1) and development of distant metastases [6].…”
Section: Introductionmentioning
confidence: 99%